Examining the Impact of Government Regulations on Financial Accountability and Risk Management in Public Sector Institutions - Pratama, Ajeng; Haedir, Ibnu; Mardiah; Pratama, Aan; Gunawan, Wahyu (Generasi Sains Indonesia, 2026)
This study examines the impact of government regulation on financial accountability and risk management in public sector institutions, addressing the need for a more integrated understanding of governance mechanisms. A quantitative explanatory design was employed, using primary data collected from 200 respondents in strategic financial roles. Data were analyzed using descriptive statistics, reliability and validity testing, multiple regression, and mediation analysis. The results show that government regulation has a strong and significant positive effect on financial accountability, enhancing transparency, internal control systems, and audit responsiveness. Government regulation also positively affects risk management, although the effect is weaker, indicating that risk practices remain largely compliance-oriented. Furthermore, financial accountability significantly influences risk management and partially mediates the relationship between government regulation and risk management. These findings highlight the interconnected nature of regulation, accountability, and risk governance. The study contributes to the literature by providing empirical evidence on integrated governance mechanisms in the public sector and suggests that improving accountability systems and institutional capacity is essential for strengthening effective risk management beyond formal regulatory compliance.